[[!toc]] #Q: How do you know that every term in the untyped lambda calculus has a fixed point?# A: That's easy: let `T` be an arbitrary term in the lambda calculus. If `T` has a fixed point, then there exists some `X` such that `X <~~> TX` (that's what it means to *have* a fixed point).
let L = \x. T (x x) in
let X = L L in
X ≡ L L ≡ (\x. T (x x)) L ~~> T (L L) ≡ T X
Please slow down and make sure that you understand what justified each of the equalities in the last line. #Q: How do you know that for any term `T`, `Y T` is a fixed point of `T`?# A: Note that in the proof given in the previous answer, we chose `T` and then set `X = L L = (\x. T (x x)) (\x. T (x x))`. If we abstract over `T`, we get the Y combinator, `\T. (\x. T (x x)) (\x. T (x x))`. No matter what argument `T` we feed `Y`, it returns some `X` that is a fixed point of `T`, by the reasoning in the previous answer. #Q: So if every term has a fixed point, even `Y` has fixed point.# A: Right:
let Y = \T. (\x. T (x x)) (\x. T (x x)) in
Y Y ≡ \T. (\x. T (x x)) (\x. T (x x)) Y
~~> (\x. Y (x x)) (\x. Y (x x))
~~> Y ((\x. Y (x x)) (\x. Y (x x)))
~~> Y (Y ((\x. Y (x x)) (\x. Y (x x))))
~~> Y (Y (Y (...(Y (Y Y))...)))
#Q: Ouch! Stop hurting my brain.# A: Is that a question? Let's come at it from the direction of arithmetic. Recall that we claimed that even `succ`---the function that added one to any number---had a fixed point. How could there be an X such that X = X+1? That would imply that X <~~> succ X <~~> succ (succ X) <~~> succ (succ (succ (X))) <~~> succ (... (succ X)...) In other words, the fixed point of `succ` is a term that is its own successor. Let's just check that `X = succ X`:
let succ = \n s z. s (n s z) in
let X = (\x. succ (x x)) (\x. succ (x x)) in
succ X 
≡ succ ( (\x. succ (x x)) (\x. succ (x x)) ) 
~~> succ (succ ( (\x. succ (x x)) (\x. succ (x x))))
≡ succ (succ X)
You should see the close similarity with `Y Y` here. #Q. So `Y` applied to `succ` returns a number that is not finite!# A. Yes! Let's see why it makes sense to think of `Y succ` as a Church numeral: [same definitions] succ X = (\n s z. s (n s z)) X = \s z. s (X s z) = succ (\s z. s (X s z)) ; using fixed-point reasoning = \s z. s ([succ (\s z. s (X s z))] s z) = \s z. s ([\s z. s ([succ (\s z. s (X s z))] s z)] s z) = \s z. s (s (succ (\s z. s (X s z)))) So `succ X` looks like a numeral: it takes two arguments, `s` and `z`, and returns a sequence of nested applications of `s`... You should be able to prove that `add 2 (Y succ) <~~> Y succ`, likewise for `mult`, `minus`, `pow`. What happens if we try `minus (Y succ)(Y succ)`? What would you expect infinity minus infinity to be? (Hint: choose your evaluation strategy so that you add two `s`s to the first number for every `s` that you add to the second number.) This is amazing, by the way: we're proving things about a term that represents arithmetic infinity. It's important to bear in mind the simplest term in question is not infinite: Y succ = (\f. (\x. f (x x)) (\x. f (x x))) (\n s z. s (n s z)) The way that infinity enters into the picture is that this term has no normal form: no matter how many times we perform beta reduction, there will always be an opportunity for more beta reduction. (Lather, rinse, repeat!) #Q. That reminds me, what about [[evaluation order]]?# A. For a recursive function that has a well-behaved base case, such as the factorial function, evaluation order is crucial. In the following computation, we will arrive at a normal form. Watch for the moment at which we have to make a choice about which beta reduction to perform next: one choice leads to a normal form, the other choice leads to endless reduction: let prefac = \f n. iszero n 1 (mult n (f (pred n))) in let fac = Y prefac in fac 2 = [(\f.(\x.f(xx))(\x.f(xx))) prefac] 2 = [(\x.prefac(xx))(\x.prefac(xx))] 2 = [prefac((\x.prefac(xx))(\x.prefac(xx)))] 2 = [prefac(prefac((\x.prefac(xx))(\x.prefac(xx))))] 2 = [(\f n. iszero n 1 (mult n (f (pred n)))) (prefac((\x.prefac(xx))(\x.prefac(xx))))] 2 = [\n. iszero n 1 (mult n ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred n)))] 2 = iszero 2 1 (mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 2))) = mult 2 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 1) ... = mult 2 (mult 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] 0)) = mult 2 (mult 1 (iszero 0 1 ([prefac((\x.prefac(xx))(\x.prefac(xx)))] (pred 0)))) = mult 2 (mult 1 1) = mult 2 1 = 2 The crucial step is the third from the last. We have our choice of either evaluating the test `iszero 0 1 ...`, which evaluates to `1`, no matter what the ... contains; or we can evaluate the `Y` pump, `(\x.prefac(xx))(\x.prefac(xx))`, to produce another copy of `prefac`. If we postpone evaluting the `iszero` test, we'll pump out copy after copy of `prefac`, and never realize that we've bottomed out in the recursion. But if we adopt a leftmost/call-by-name/normal-order evaluation strategy, we'll always start with the `iszero` predicate, and only produce a fresh copy of `prefac` if we are forced to.